EMPIRICAL REVISITING OF THE MACEDONIAN MTPL INSURANCE CASE AND THE UNDERLYING FACTORS OF INFLUENCE - Peovski, Filip; Ivanovski, Igor; Ahmedi, Sulejman (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2022)
Motor third-party liability insurance (MTPL) remains one of the dominant insurance classes in the Macedonian economy even besides the government regulated tariff system imposed. Pinpoint the key variables of interest has spurred debates for a prolonged period but without growing results in global literature, decreasing the ability to observe relationships important for the future liberalized system. Through a fixed effects panel regression this paper estimates the impact of MTPL premiums, claims, number of contracts, and market share on MTPL premium dynamics during the 2012-2021 period. The Macedonian empirical case suggests that the previous period number of contracts is not a significant determinant, unlike others. A positive impact is noted for the number of claims per contract, one period lagged MTPL premium per contract and MTPL concentration of the market. Adverse influence is found for the share of MTPL insurance in total GWP per company, one period lagged claims per contract and the market concentration of MTPL claims. Such observations help us understand the underlying forces in a non-liberalized MTPL market and propose business expectations for the future.
Keywords: MTPL insurance, finance, panel regression